Functional features of a novel interferon-stimulated gene SHFL: a comprehensive review - Wang, Xingzheng; Zhang, A-Mei (Frontiers in Microbiology, 2023)
Various interferon (IFN)-stimulated genes (ISGs), expressed via Janus kinase–signal transducer and activator of transcription (JAK-STAT) signaling pathway-stimulated IFNs to increase antiviral effects or regulate immune response, perform different roles in virus-infected cells. In recent years, a novel ISG, SHFL, which is located in the genomic region 19p13.2 and comprises two isoforms, has been studied as a virus-inhibiting agent. Studies have shown that SHFL suppressive effects on human immunodeficiency virus-1 (HIV), Zika virus (ZIKV), dengue virus (DENV), hepatitis C virus (HCV), Japanese encephalitis virus (JEV), porcine epidemic diarrhea virus (PEDV), Human enterovirus A71 (EV-A71) and Kaposi’s sarcoma-associated herpes virus (KSHV). SHFL interacts with various viral and host molecules to inhibit viral life circle and activities, such as replication, translation, and ribosomal frameshifting, or regulates host pathways to degrade viral proteins. In this review, we summarized the functional features of SHFL to provide insights to underlying mechanisms of the antiviral effects of SHFL and explored its potential function.